2002
DOI: 10.1046/j.1096-3642.2002.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary relationships of euthyneuran gastropods (Mollusca): a cladistic re-evaluation of morphological characters

Abstract: Morphological characters of the Euthyneura available from the literature were re-evaluated in terms of terminology and primary homology. A total of 77 characters and 75 taxa were retained in a data matrix. Several assumptions on character weights and types were tested. In the cladistic analyses, it appeared that the data matrix was highly homoplastic, and only robust nodes (those which were little modified by variations in weight and coding of characters) were retained in a concensus tree. The evolutionary his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(136 citation statements)
references
References 196 publications
11
122
2
1
Order By: Relevance
“…Solem (1978) classified Onchidiidae, Veronicellidae, and Rathouisiidae in the Systellommatophora. Dayrat and Tillier (2002) could not find synapomorphies to support the monophyly of Systellommatophora. The pedal gland at the bottom of the anterior visceral cavity (exclusively found in onchidiids and veronicellids) could be a diagnostic synapomorphy of Systellommatophora; also, the presence of eyes at the tip of the cephalic tentacles could have been acquired twice independently (once in the common ancestral lineage to Systellommatophora, and once in the common ancestral lineage to Stylommatophora).…”
Section: Evolution Of Systellomatophoramentioning
confidence: 80%
See 2 more Smart Citations
“…Solem (1978) classified Onchidiidae, Veronicellidae, and Rathouisiidae in the Systellommatophora. Dayrat and Tillier (2002) could not find synapomorphies to support the monophyly of Systellommatophora. The pedal gland at the bottom of the anterior visceral cavity (exclusively found in onchidiids and veronicellids) could be a diagnostic synapomorphy of Systellommatophora; also, the presence of eyes at the tip of the cephalic tentacles could have been acquired twice independently (once in the common ancestral lineage to Systellommatophora, and once in the common ancestral lineage to Stylommatophora).…”
Section: Evolution Of Systellomatophoramentioning
confidence: 80%
“…More recently, Otina was considered to be closely related to onchidiid and veronicellid slugs (Haszprunar and Huber, 1990) or stylommatophorans (Tillier and Ponder, 1992). Dayrat and Tillier (2002) showed that morphological data fail to resolve the relationships of Otina. The opening of the membrane gland into the carrefour (Dayrat and Tillier, 2002), which is found only in some (but not all) ellobiids and Otina, is a potential synapomorphy for that clade.…”
Section: Evolution Of Ellobiidae (Including Otina Smeagol Trimusculus)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have dealt with opisthobranch phylogeny in general (Gosliner 1981;Schmekel 1985;Salvini-Plawen 1990Salvini-Plawen and Steiner 1996;Dayrat and Tillier 2002;Mikkelsen 2002;Wägele and Klussmann-Kolb 2005) (Fig. 2b-d); however, without recovering completely congruent and convincing topologies.…”
Section: Classification and Phylogenetic Concepts Of Opisthobranchia mentioning
confidence: 99%
“…He based his ideas about molluscan systematics on anatomical information taken from Lacaze-Duthiers (1870, after Dayrat and Tillier 2002) and his own examinations of nervous systems. Von Ihering united Opisthobranchia (including the Rhodopidae, a taxon he described in 1876) and Pulmonata within his new taxon Ichnopoda, which comprised many heterobranchs.…”
Section: Late Nineteenth Centurymentioning
confidence: 99%